THE IMPACT OF NURSING STRATEGIES ON OCCUPATIONAL BURNOUT AND STRESS (International Journal of Food and Nutritional Sciences, 2022)
Nursing staff play a crucial role in healthcare systems, providing essential care and support to patients. Despite their critical contributions, they face significant psychological and manpower challenges that can impact their well-being and job performance A mixed-methods approach was employed to gather comprehensive data. Quantitative data were collected through surveys distributed to a diverse sample of nursing staff across various healthcare settings. These surveys assessed levels of job stress, burnout, job satisfaction, and perceived adequacy of staffing. The study highlights the complex interplay between psychological and manpower challenges faced by nursing staff. By identifying these challenges, the research provides a foundation for developing comprehensive support systems and policies aimed at improving the well-being and effectiveness of nursing staff.